Pengembangan Kemampuan Self-Regulated Learning (SRL) pada Peserta Didik Sekolah Dasar Berasrama - Kibtiyah, Asriana; Gunadi, Ikhsan; Umam, Khoirul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research is based on the phenomenon of learning outcomes experienced by each student. Learning achievements are meant not only in academic fields marked by numbers/grades on the study evaluation results sheet but also in non-academic fields with a broader scope. SD Plus Mutiara Ilmu which carries the concept of multiple intelligences already uses educational principles according to the latest curriculum guidelines. In addition, the existence of schools with a relatively low level of public awareness of education can make proud achievements. Interestingly, this school has a dormitory for students who come from out of town. This phenomenon is interesting to explore further considering that the existence of elementary education level education units is still quite rare with dormitories. This study uses a qualitative-descriptive approach with data collection using oral interview techniques and field observations. The results of the study showed that some students had SRL abilities, especially those who had achieved learning achievements at school and in the dormitories.